The Role of Entrepreneurial Competence in Mediating Social Media Utilization and E-Payment Services on Marketing Performance in West Java Culinary MSMES - Syahrul Ahmad Gunawan; Syti Sarah Maesaroh; Adi Prehanto (Eduvest - Journal of Universal Studies, 2024)
This study looks into how entrepreneurial skill influences the relationship between the usage of social media, e-payment systems, and marketing performance in culinary MSMEs in West Java. This study used the associative causal method to evaluate data received from 400 MSME respondents using a structural equation model (SEM) and SmartPLS 3.0 software. The findings indicate that the usage of social media and e-payment systems improves marketing performance both directly and indirectly, with entrepreneurial competence serving as a significant mediating factor. This study emphasizes the significance of integrating digital technologies and developing entrepreneurial skills in order to attain competitive marketing performance in the digital era. Training programs aimed at boosting MSME actors' digital literacy and entrepreneurial abilities are recommended